Drama Learning Using the Role Play Method in Script Performances “Jangan Buang Sampah Sembarangan” in Lower Grade Elementary School: Pembelajaran Drama menggunakan Metode Role Play dalam Pementasan Naskah “Jangan Buang Sampah Sembarangan” anak kelas tingkat bawah Sekolah Dasar - Andy Robby Iftida Amri; Evie Destiana (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the learning process of drama extracurricular at the Primary School Lab School, State University of Surabaya using the role play method. This study uses a qualitative approach with a descriptive study type by observing the drama learning process using the role play method and drama performances using a script, don't litter at school art performances which are held regularly once a year. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is data reduction such as selecting and classifying the findings needed so that they do not widen from the core of the discussion, presenting data from the findings of the training process to staging, and drawing conclusions from all findings. The results showed that learning drama by using the role play method, got satisfactory results because from these results students were able to appear confident and able to perform well in performing arts performances held at school.